Effects of chronic isovolaemic haemodilution on regional cerebral blood flow in conscious rats - Frietsch, Thomas; Lenz, Christian; Kuschinsky, Wolfgang; Waschke, Klaus F. (European journal of anaesthesiology, 2004)
Background and objective: - Acute isovolaemic haemodilution increases local and mean cerebral blood flow. It is not known whether a single haemodilution has a short-term effect only or whether it affects cerebral perfusion over a longer time period. In the present study, local and mean cerebral blood flow were determined in conscious rats after a 4, 24 and 48 h period following one-time haemodilution. - Methods: - Thirty-six rats were randomized to three untreated sham groups and three groups of haemodilution (4, 24 or 48 h, n = 6 for each group). Isovolaemic haemodilution with albumin 5% aimed to a target haematocrit of 0.2. Local cerebral blood flow was measured in 38 brain regions by the iodo-[14C]antipyrine method in conscious normothermic rats. - Results: - Isovolaemic haemodilution reduced haematocrit from 0.44 to 0.20. During the following 24 and 48 h periods, haematocrit remained low (0.22 and 0.21). Mean cerebral blood flow was similar in untreated sham groups (88 ± 12 after 4 h, 92 ± 11 after 24 h, 96 ± 10 mL 100 g−1 min−1 after 48 h). Haemodilution increased mean cerebral blood flow after 4 h (184 ± 11 mL 100 g−1 min−1), after 24 h (153 ± 13 mL 100 g−1 min−1) and 48 h (149 ± 15 mL 100 g−1 min−1) (P ≤ 0.05). Local cerebral blood flow increased in all 38 structures after 4 h haemodilution but decreased with time in six of 38 brain structures after 24 h and in 15 regions after 48 h (P ≤ 0.05). - Conclusions: - A single one-time haemodilution increased mean cerebral blood flow for 2 days. However, local adaptation of cerebral blood flow to a chronic low haematocrit occurred but was heterogeneous within the brain.
Gesehen am 05.05.2021